Magnetars: the explosive character of a small class of strongly magnetized neutron stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Rea, Nanda
Abstract: I will review our current knowledge on the most magnetic objects in the Universe, a small sample of neutron stars called magnetars. The powerful persistent high energy emission and the flares from these strongly magnetized (10 15 Gauss) neutron stars are providing crucial information about the physics involved at these extremes conditions, reserving us many unexpected surprises.